Combined targeting EGFR and SRC as a potential novel therapeutic approach for the treatment of triple negative breast cancer. (January 2020) - Canonici, Alexandra; Browne, Alacoque L.; Ibrahim, Mohamed F. K.; Fanning, Kevin P.; Roche, Sandra; Conlon, Neil T.; O'Neill, Fiona; Meiller, Justine; Cremona, Mattia; Morgan, Clare; Hennessy, Bryan T.; Eustace, Alex J.; et al.
Background: Triple negative breast cancer (TNBC) is an aggressive subtype of breast cancer with limited therapeutic options. Epidermal growth factor receptor (EGFR) has been shown to be over-expressed in TNBC and represents a rational treatment target. Methods: We examined single agent and combination effects for afatinib and dasatinib in TNBC. We then determined IC50 and combination index values using Calcusyn. Functional analysis of single and combination treatments was performed using reverse phase protein array and cell cycle analysis. Finally, we determined the anticancer effects of the combination in vivo . Results: A total of 14 TNBC cell lines responded to afatinib with IC50 values ranging from 0.008 to 5.0 µM. Three cell lines, belonging to the basal-like subtype of TNBC, were sensitive to afatinib. The addition of afatinib enhanced response to the five other targeted therapies in HCC1937 and HDQP1 cells. The combination of afatinib with dasatinib caused the greatest growth inhibition in both cell lines. The afatinib/dasatinib combination was synergistic and/or additive in 13/14 TNBC cell lines. Combined afatinib/dasatinib treatment induced G1 cell cycle arrest. Reverse phase protein array results showed the afatinib/dasatinib combination resulted in efficient inhibition of both pERK(T202/T204) and pAkt(S473) signalling in BT20 cells, which was associated with the greatest antiproliferative effects. High baseline levels of pSrc(Y416) and pMAPK(p38) correlated with sensitivity to afatinib, whereas low levels of B-cell lymphoma 2 (Bcl2) and mammalian target of rapamycin (mTOR) correlated with synergistic growth inhibition by combined afatinib and dasatinib treatment. In vivo, the combination treatment inhibited tumour growth in a HCC1806 xenograft model. Conclusions: We demonstrate that afatinib combined with dasatinib has potential clinical activity in TNBC but warrants further preclinical investigation.